Leaf development in three maize cultivars in two planting dates - Noldin, José Alberto; Mundstock, Claudio Mario (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was conducted at the EEA/UFRGS, located in Guaíba, Rio Grande do Sul State, Brazil, during 1984/85, to study the effects of two planting dating dates (8.10.84 and 11.1.85) on leaf development (leaves number, size, area and appearance rates) of three maize (Zea mays L)cultivars (Agroceres 280, Cargill 408, Pioneer 6872). As planting was delayed plant leaf area was little affected and some of the variations, according to the genotype, was due to leaf number (decreased in Agroceres 28C and Cargill 408), expansion (increased in Agroceres 28C and Pioneer 6872) and senescence. The plant leaf area profile was not affected by genotype or planting date. The biggest leaves were located around the ear insertion node. Leaves number was higher in the late cultivars and maximum leaf area occurred at silking stage.